HUBUNGAN ANTARA TINGKAT STRES DAN KECEMASAN DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI KLINIK ISLAMIC CENTER SAMARINDA - Annaas Budi Setyawan (Universitas Muhammadiyah Kalimantan Timur, 2017)
Except aging process to elderly, stress and anxiety is factors which is can not be avoided from human life and factors which cause hypertension. On high blood pressure, heart pump out blood with extreme high pressure, it because of some factors which are stress and anxiety. Increasing of blood pressure will be bigger to individual who tend to be stress and high emotional anxiety. This research was to know relationship between stress level and anxiety with incidence to elderly on Islamic Center Clinic Samarinda.This research method used qualitative design with cross-sectional approaching. Population on this research are 103 respondents. Sample collection on this research using slovin formula, then got 82 respondents. Sample selection used Accidental Sampling method. This research used correlation statistic test spearman ranks. This research result showed there was relationship between stress level and anxiety with hypertension incidence which got significant result score p value p=0,000 < 0,05, that there was significant relationship between stress and anxiety level with heavy hypertension incidence to respondents elderly.